2012
DOI: 10.5830/cvja-2011-030
|View full text |Cite
|
Sign up to set email alerts
|

Early diastolic functional abnormalities in normotensive offspring of Nigerian hypertensives

Abstract: BackgroundSome studies have suggested that diastolic dysfunction precedes the clinical manifestation of hypertension. Whether changes in cardiac structure and function predate the clinical manifestation of hypertension later in life is now being investigated. The aim of this study was to assess the differences in cardiac structure and function between the offspring of hypertensive and normotensive parents.MethodsEighty normotensive offspring of hypertensive parents (OHyp) (41 females and 39 males) and 62 normo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
1
6
2
Order By: Relevance
“…Thus, the heart does more work in pushing blood against the thickened arterial wall leading to an increase in arterial blood pressure. 44,51 However, our study did not show any signi cant gender difference in the occurrence of hypertension although a systematic review on the current prevalence and pattern of hypertension in Nigeria reported higher prevalence of hypertension among males compared to females 44,45,52,53 . Being employed and having dyslipidaemia were other predictors of hypertension in this study.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Thus, the heart does more work in pushing blood against the thickened arterial wall leading to an increase in arterial blood pressure. 44,51 However, our study did not show any signi cant gender difference in the occurrence of hypertension although a systematic review on the current prevalence and pattern of hypertension in Nigeria reported higher prevalence of hypertension among males compared to females 44,45,52,53 . Being employed and having dyslipidaemia were other predictors of hypertension in this study.…”
Section: Discussioncontrasting
confidence: 80%
“…However, lower prevalence of physical activity (37.8%) among civil servants in Ibadan have been reported. 44,45 The differences in the ndings could be due to the subjective method of assessment in self-reported questionnaires. 46 Meanwhile, this study used WHO recommendation to classify participants into physical activity categories.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Lagos is a boisterous city and residents have to engage in demanding jobs and travel long distance daily in search of their daily means of sustenance. However, lower prevalence of physical activity (37.8%) among civil servants in Ibadan have been reported [40,41]. The differences in the findings could be due to the subjective method of assessment in self-reported questionnaires [42].…”
Section: Discussionmentioning
confidence: 90%
“…In a study by Dupont et al ., spontaneously hypertensive rats (SHR) demonstrated early LV diastolic dysfunction before the onset of hypertension and LV hypertrophy (LVH) (Dupont et al ., ). A Nigerian study on normotensive offspring of hypertensive parents revealed that diastolic dysfunction precedes clinical hypertension in genetically predisposed individuals, without evidence of LVH (Adeoye et al ., ).…”
Section: The Hypertension Linkmentioning
confidence: 97%